2020
DOI: 10.1200/jco.2020.38.15_suppl.e19512
|View full text |Cite
|
Sign up to set email alerts
|

The comparative effectiveness of glasdegib in combination with low-dose cytarabine versus azacitidine by bone marrow blasts counts among patients with newly-diagnosed acute myeloid leukemia who are ineligible for intensive chemotherapy.

Abstract: e19512 Background: Acute myeloid leukemia (AML) is an orphan disease with one of the lowest five-year survival rates among myeloid malignancies. Recently, a randomized, open label study among previously untreated, chemotherapy-ineligible AML patients demonstrated improved overall survival (OS) among patients treated with glasdegib (GLAS) + LDAC compared with LDAC alone. Two trials of AZA vs. conventional care regimens report data by bone marrow blast (BMB) counts: one with 20-30% and the other with >30%. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on this methodology, glasdegib associated with LDAC tended to demonstrate consistently favored OS hazard ratios (HR) over either AZA or decitabine (HR = 0.424; 95 % CI = 0.228-0.789 and HR = 0.505; 95 % CI = 0.269-0.949, respectively). A second study performed an indirect treatment comparison between glasdegib + LDAC and AZA depending on bone marrow blasts count (77). Both unadjusted HRs and HRs corrected for the potential imbalances at baseline between the trials suggested that glasdegib + LDAC association may be preferred over AZA, regardless of bone marrow blasts count, in previously untreated, chemotherapy-ineligible AML patients.…”
Section: Phase IImentioning
confidence: 99%
“…Based on this methodology, glasdegib associated with LDAC tended to demonstrate consistently favored OS hazard ratios (HR) over either AZA or decitabine (HR = 0.424; 95 % CI = 0.228-0.789 and HR = 0.505; 95 % CI = 0.269-0.949, respectively). A second study performed an indirect treatment comparison between glasdegib + LDAC and AZA depending on bone marrow blasts count (77). Both unadjusted HRs and HRs corrected for the potential imbalances at baseline between the trials suggested that glasdegib + LDAC association may be preferred over AZA, regardless of bone marrow blasts count, in previously untreated, chemotherapy-ineligible AML patients.…”
Section: Phase IImentioning
confidence: 99%
“…There are no direct, head-to-head comparisons available comparing glasdegib þ LDAC and azacitidine. Therefore, this study relied on the indirect treatment comparisons (ITCs) conducted in a recent publication 12 , where OS was statistically compared between glasdegib þ LDAC and azacitidine via the common comparator LDAC alone by BMB (Table 1). These HRs were further applied to the OS curve of glasdegib þ LDAC in each BMB subgroup to derive the OS curve of azacitidine ( Figure 2).…”
Section: Efficacy Measuresmentioning
confidence: 99%
“…OS HRs of glasdegib þ LDAC versus azacitidine obtained from a previous publication12 . GLAS þ LDAC vs. LDAC AZA vs. LDAC GLAS þ LDAC vs. AZA 20-30% BMB 0.17 [0.06-0.48] 0.37 [0.12-1.13] 0.46 [0.10, 2.14] >30% BMB 0.62 [0.38, 1.02] 0.90 [0.70, 1.16] 0.69 [0.39, 1.20] Remarks HR in favor of GLAS þ LDAC HR in favor of AZA HR in favor of GLAS þ LDAC Abbreviations: AZA, azacitidine; BMB, bone marrow blasts; GLAS, glasdegib; HR, hazard ratio; LDAC, low-dose cytarabine; NMA, network meta-analysis; OS, overall survival.…”
mentioning
confidence: 99%
“…[36][37][38][39][40] After the FDA approval of glasdegib, certain comparative analyses found a possible survival advantage with glasdegib/LDAC vs HMA monotherapy. 41,42 The treatment landscape changed in 2018 when the oral BCL2 inhibitor venetoclax was approved in combination with an HMA or LDAC in the treatment of newly diagnosed in AML in patients aged 75 years or older or who have comorbidities that preclude use of intensive induction chemotherapy. The Phase 1b trial leading to approval and the confirmatory Phase 3 VIALE-A trial, which compared azacitidine/venetoclax to azacitidine/placebo, showed previously unprecedented CR/Cri rates of 66-74% and median OS 16.9 months with nonintensive therapy.…”
mentioning
confidence: 99%